Binding pipelines? Oil, armed conflicts, and economic rationales for peace in the two Sudans. Issue 2 (3rd May 2016) - Le Billon, Philippe; Savage, Emily
Abstract : The independence referendum of South Sudan in 2011 brought about the birth of a new land-locked and oil export-dependent African country. Despite obvious challenges, there was hope that oil could fund South Sudanese development, and that mutual economic dependence on a thriving oil sector would incentivize peaceful bilateral relations between South Sudan and Sudan. Yet, within six months of independence, tensions escalated, Sudan leveraged its control of oil export infrastructure to demand hefty transit payments and an end to South Sudanese support to rebels in the north, with South Sudan responding by shutting down its oil production and seeking alternative pipeline routes. Domestically, the mismanagement of oil revenues and shutdown of oil production also exacerbated tensions within the South Sudanese Government, contributing to its breaking apart and renewed civil war in December 2013. In contrast to optimistic views of oil-fuelled peace incentives, we point at the challenging political geography of oil in the two Sudans and the tensions undermining economic logics of 'mutual interests' and 'peace dividends' between, and within, these two countries.